My_Watch - changing the way we use watches / Nur Athilla Alimin ... [et al.] - Alimin, Nur Athilla; Zainudin, Nur Hadirah Faqihah; Suhairi, Siti Nadiah Afiqah; Rumpungan Jr, Joseph Joshua; Aziz, Adrianna (2021)
The demand for QR codes in this digital era has increased as we need to scan for QR codes everywhere we go. Due to Covid-19 pandemic, the usage of QR code is to comply with the current Standard Operating Procedure required by the Ministry of Health in Malaysia. Hence, My_Watch aims to foster convenience for everyone by enabling QR Codes to be scanned by using only our smartwatch and eliminate the hassle of using your phones and decrease the chances of contaminating it. This product is designed to encourage the contactless method, especially where it is mostly the new norm of our current lifestyle, and it also efficiently saves time especially speeding up the queuing line and process of checking in at entry points of a place. Not to forget that technology is constantly evolving, and we should strive to stay updated. We can keep up with the current technology by integrating the use of My_Watch into our daily life. The current smartwatch available on the market still features limited perks and does not allow scanning of QR Codes whereas My_Watch highlights its added camera and other smart features to enable face recognition, voice recognition, QR Code Scanner, and simplify the use of e-wallet all the while to be more sustainable by using a solar-powered battery. This improved smartwatch changes our daily regimen for the better as it can simplify our life and add convenience to the whole community. Time spent on trivial matters also decreases and furthermore it can assist us in coping with the new norms and catching up with the latest technology advancement. Everyone utilizes a watch therefore it will be easier to integrate the use of this product into our daily life.